Dealkenylation of neoandrographolide, a phytochemical from Andrographis paniculata stimulates FXR (Farnesoid X Receptor) and enhances gallstone dissolution. Issue 8 (24th May 2023) - Sharma, Rajani; Kumar, Kunal; Tanvi, Kumari
Abstract: FXR (Farnesoid X Receptor) is one of the nuclear receptors expressed in the liver performing a significant role in the maintenance of bile acid concentration. An imbalance of cholesterol and bile acid ratio due to any undefined reason could cause gallstone formation. Hence, this paper aims to screen phytochemicals that could maintain a requisite balance of cholesterol and bile acid by targeting FXR and thereby contributing to the dissolution of gallstone. Nineteen phytochemicals were selected and queried for Pa and Pi in the way2drug online server for hepatoprotective property, cholesterol synthesis and absorption inhibition property, and β-glucuronidase inhibiting activity. Cianidanol, neoandrographolide, cynarine, saponins, and tanins with satisfying stated properties were docked with the screened FXR (PDB ID- 1OSH) using HADDOCK server, followed by pharmacokinetics study utilizing SwissADME tool. Neoandrographolide fits best among the other selected literature-based phytochemicals with minor violation of 'Brenk's rule'. The violation was corrected with the removal of an alkene group in the provided ChemDraw space of SwissADME. This Dealkenylated compound was further docked with FXR. The promising response under the static condition of the Dealkenylated compound was analyzed for molecular dynamic simulation at physiological conditions for 100 ns. Dealkenylated Neoandrographolide (DN) exhibited hepatoprotective, cholesterol synthesis and absorption inhibition property, and β-glucuronidase inhibition activity with a superior binding score of −42.6+/-1.5 with FXR. The interaction of the FXR receptor and the DN showed exceptional stability at physiological conditions during MD simulation and fit for the ADME properties, therefore it could be a potent candidate to dissolve gallstones. Communicated by Ramaswamy H. Sarma.